OPTIMASI EFISIENSI ENERGI PADA MOBIL LISTRIK EMPAT PENUMPANG MELALUI SISTEM REGENERATIVE BRAKE - Handayani, Dwi (Jurnal Ilmiah Teknik Industri, 2024)
The continuous use of fossil energy can have an impact on the energy crisis and environmental pollution Greenhouse Gas (GHG) is a contributing factor to climate change. Electric cars are one of the solutions to these problems. Because electric cars use clean and renewable electrical resources to drive their vehicles, they can reduce dependence on limited fossil fuels. In the use of electric cars that utilize regenerative braking technology, the first stage is to design the portion of mechanical braking on both the front and rear wheels, along with regenerative braking. The goal is to obtain a safe braking portion by following the ideal braking upper limit that has been set, as well as the lower limit set by the ECE braking standard. After obtaining a safe braking portion that is in accordance with actual conditions, the next step is to find the energy generated by the regenerative braking system by simulating it using Matlab-simulink. In this simulation, the regenerative brake efficiency can be obtained by comparing the absorbed energy and the available braking energy. The regenerative brake system in this study is able to absorb 1.7623 kWh of energy with an efficiency of 67.31% at a regenerative braking portion of 0.137 and front mechanical braking of 0.6629 at a road friction coefficient of 0.8.